Edge‐Cutting Transfer: Deterministic Assembly of Flexible Si/Ge Nanoribbons via Edge‐Cutting Transfer and Printing for van der Waals Heterojunctions (Small 33/2015). Issue 33 (September 2015) - Guo, Qinglei; Zhang, Miao; Xue, Zhongying; Wang, Gang; Chen, Da; Cao, Ronggen; Huang, Gaoshan; Mei, Yongfeng; Di, Zengfeng; Wang, Xi
<x xml:space="preserve">Abstract</x> A combined and controlled approach called edge‐cutting transfer (E‐CT) is used on page 4140 by Y. Mei, Z. Di, and co‐workers to precisely generate spatially aligned Si/Ge nanoribbons with a designed geometry. The suspended nanoribbons are formed by the selective etching of a buried oxide layer, then a slab of cured PDMS is contacted with the patterned donor source. Pulling away the PDMS cuts the suspended Si/Ge nanoribbons off the substrate in a controllable manner, obtaining Si/Ge nanoribbon arrays on a flexible PDMS substrate.